2015
DOI: 10.1371/journal.pone.0130755
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Cell-Derived Respiratory Syncytial Virus-Like Particles Protect the Lower as well as the Upper Respiratory Tract

Abstract: Globally, Respiratory Syncytial Virus (RSV) is a leading cause of bronchiolitis and pneumonia in children less than one year of age and in USA alone, between 85,000 and 144,000 infants are hospitalized every year. To date, there is no licensed vaccine. We have evaluated vaccine potential of mammalian cell-derived native RSV virus-like particles (RSV VLPs) composed of the two surface glycoproteins G and F, and the matrix protein M. Results of in vitro testing showed that the VLPs were functionally assembled and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…As multiple host factors are likely involved in hRSV VLP assembly, host species and/or cell-type-specific differences for optimal VLP production may come into play and will have to be analyzed and optimized, depending on the cell culture system of choice. A recent paper reported that immunogenic VLPs were isolated from HEK293 cells coexpressing the M, G, and F proteins (58). Our present work would predict that in the absence of P, coalescence of M, F, and G proteins and VLP formation are not optimal and that the efficiency could be enhanced by including P. However, the systems are not readily compared, as the VLPs produced by M-G-F coexpression were spherical and were harvested at a much later time point from suspensions of HEK293 cells at ultrahigh g force, whereas we focused on cell-associated filamentous VLPs at an earlier time point to avoid potential morphological changes associated with purification, as well as excessive cell lysis and/or death.…”
Section: Discussionmentioning
confidence: 99%
“…As multiple host factors are likely involved in hRSV VLP assembly, host species and/or cell-type-specific differences for optimal VLP production may come into play and will have to be analyzed and optimized, depending on the cell culture system of choice. A recent paper reported that immunogenic VLPs were isolated from HEK293 cells coexpressing the M, G, and F proteins (58). Our present work would predict that in the absence of P, coalescence of M, F, and G proteins and VLP formation are not optimal and that the efficiency could be enhanced by including P. However, the systems are not readily compared, as the VLPs produced by M-G-F coexpression were spherical and were harvested at a much later time point from suspensions of HEK293 cells at ultrahigh g force, whereas we focused on cell-associated filamentous VLPs at an earlier time point to avoid potential morphological changes associated with purification, as well as excessive cell lysis and/or death.…”
Section: Discussionmentioning
confidence: 99%
“…RSV VLP vaccination of mice induced neutralizing antibodies, correlating with reducing lung viral loads and protection in mice after RSV challenge infection [101]. RSV VLPs composed of RSV G, F, M proteins elicited high titers of IgG antibody responses to homologous RSV A2 and heterologous RSV B strain challenge [102]. Mammalian cell-derived RSV VLP vaccines adjuvanted with combination of alum and monophosphoryl lipid A induced higher levels of IgG titers than non-adjuvanted VLPs [102].…”
Section: Vaccine Efficacy Of Rsv Vlp Vaccinesmentioning
confidence: 98%
“…RSV F VLPs displayed a range of size distribution at approximate 80-100 nm in diameter, whereas G-VLPs were similar but somewhat more heterogeneous in size [101]. RSV VLPs were also reported to be generated by transfection of mammalian HEK293 cells with three types of expression plasmids, containing codon optimized RSV-G, F and M proteins [102]. RSV VLPs appear to mimic native RSV in morphology and structure, as examined by transmission electron microscopy.…”
Section: Rsv Vlp Vaccine Components and Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their size, they share some properties with NPs; for example, they can enter freely into the lymphatic vessel and reach the draining lymph nodes [9]. Several platforms for producing VLPs have been employed to develop RSV vaccines carrying the F, G and/or M2 proteins, such as insect cells [10,90,91], mammalian cells [11,92,93,94], plant expression system [95,96], bacteria [97,98] and in vitro cell-free systems [8,99]. A variety of VLP-based RSV vaccines has been developed and tested in the last decade.…”
Section: The Particle Materialsmentioning
confidence: 99%